A Rheme of One’s Own: How ‘Original’ do we Expect Students to be? - Johnson, A.; Clerehan, R. (Journal of University Teaching and Learning Practice, 2005)
Current discussions of plagiarism in the university have taken something of a criminological turn. At the same time, there is a tendency to focus on technological solutions. Against these trends, we argue that plagiarism remains, fundamentally, a philosophical and pedagogical issue for universities, related to understanding the meaning of originality and using sources for different disciplines. Toward this goal we place the notion of originality in its historical and disciplinary contexts, and question the view that it is a natural and universal quality of good writing. The practice of assessing undergraduate students on their ability to produce ‘original’ texts depends on a notion of originality that is unstable and uncertain. We examine a sample of statements about originality given to students and explore the nature of the demands placed on student writers in the internationalised university.